The Council of the Thebaid, 362: Lucifer of Calaris, Eusebius of Vercellae, and the Readmission of the Clergy - Fiano, Emanuel (The journal of ecclesiastical history, 2022)
This article focuses on the Council of the Thebaid of 362. A close examination of Theodoret's version of events reveals that, upon the recall of the pro-Nicenes from exile, Eusebius of Vercellae organised in the Thebaid a non-rigorist meeting, which laid the groundwork for the Council of Alexandria of the same year. The Council of the Thebaid may have also included lapsed pro-Nicenes who had reverted to their original views after being deposed at Constantinople in 360, and may even have seen the participation of members of the homoiousian alliance.